Moisture-induced degradation of interfacial bond in FRP-strengthened masonry - Maljaee, Hamid (2016)
Externally bonded strengthening of masonry structures using Fiber Reinforced Polymers (FRPs) has been accepted as a promising technique. Although the effectiveness of FRPs in improving the performance of masonry components has been extensively investigated, their long-term performance and durability remain poorly addressed. This paper, tackling one of the aspects related to durability of these systems, presents an experimental investigation on the effect of long-term (one year) water immersion on the performance of GFRP-strengthened bricks. The tests include materials' mechanical tests, as well as pull-off and single-lap shear bond tests, to investigate the changes in material properties and bond behavior with immersion time, respectively. The effect of mechanical surface treatment on the durability of the strengthened system as well as the reversibility of the degradation upon partial drying are also investigated. The experimental results are presented and critically discussed.